SISTEM INFORMASI PENDATAAN KLIEN JARINGAN PADA LOKASI TERDISTRIBUSI MENGGUNAKAN PHP DAN MYSQL - Ari Kaesar Putra; Agus Alim; Cecep Kurnia Sastradipraja (Jurnal Teknologi Komputer dan Informatika, 2025)
Telecommunication operators face significant challenges in Monitoring Optical signal quality across thousands of fiber optik subscribers in real-time, resulting in delayed problem detection of 2-4 hours and increased operational costs. This study develops a web-based Fiber optik Monitoring system using Waterfall development model with PHP, MySQL, and Chart.js technologies to provide real-time visualization and automated alert mechanisms. The system was implemented through five sequential phases: requirement analysis, system design, implementation, testing with synthetic dataset simulation from 50+ ONU devices generating 5,000+ data points over 100 hours, and evaluation across three operational scenarios. Implementation results demonstrate average response time of 200ms, Monitoring accuracy of 99.9% validated through Kolmogorov-Smirnov test (p=0.342), and 97.5% faster problem detection reducing detection time from 2-4 hours to less than 5 minutes. The system successfully handles 300 concurrent users with degradation trend analysis achieving R²=0.9987 and optimal alert threshold at -30 dBm, proving to be a viable and cost-effective solution for telecommunication Network Management. Keywords: Fiber optik Monitoring; GPON; Real-time Dashboard; OLT/ONU; PHP; MySQL.